FEDERALISM OR A UNITARY STATE AS A STRATEGIC CHOICE AND ITS CONSEQUENCES (COMPARATIVE ANALYSIS OF RUSSIA AND KAZAKHSTAN) - Irina M. Busygina; Elmira Taukebaeva (Сравнительная политика, 2015)
After the collapse of theSoviet Unionand the raise of new independent states a question of choosing the format of center-regions relationship became crucial. Political elites ofRussiaandKazakhstanmade completely different choices:Russia— in favor of a federal state, whereasKazakhstansupported the idea of a unitary state. These decisions were made more than 20 years ago and it is now possible to evaluate the consequences of these choices in both states.